Pemberian Akupresur terhadap Perubahan Nilai Glasgow Coma Scale (GCS) pada Pasien Penurunan Kesadaran - Andri, Juli; Padila, Padila; Sugiharno, Ramadhan Trybahari; Bura, Jeri; Ardiansa, Ardiansa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of acupressure on changes in Glasgow Coma Scale (GCS) values in patients with decreased consciousness. The research design used was a quasi-experiment, one group pre-test, and a post-test design. The results of the univariate analysis showed that before the acupressure intervention, the majority of respondents (23.3%) were at the somnolent level of consciousness, and after the intervention, the majority of respondents, six people (20.0%), were at the delirium level of consciousness. The results of bivariate analysis showed that the p-value (0.004). In conclusion, acupressure has an effect on changes in GCS values in patients with decreased consciousness. Keywords: Acupressure, Glasgow Coma Scale (GCS)